A comparison of strain and fluid shear stress in stimulating bone cell responses - a computational and experimental study - Prendergast, Patrick (My University, 2005)
Bone undergoes continuous remodeling in response to mechanical loading. However, the underlying mechanisms by which bone cells respond to their changing mechanical environment, that is, strain in the load-bearing matrix or fluid flow through the canalicular network, are not well understood. It has been established in vitro that bone cells respond differently to substrate strain and fluid shear stress treatments. Uncovering the mechanical basis of these differences represents a significant challenge to our understanding of cellular mechanotransduction and bone remodeling. To investigate this problem, we developed a biomechanical model of an adherent cell, to test the hypothesis that bone cells respond differently to 0.6 Pa fluid shear stress and 1,000 mu(epsilon) substrate strain stimulation because of qualitative and quantitative differences in the cellular deformation caused. Fluid shear stress loading conditions resulted in maximum displacements at the apical surface of the cell approximately 8 times higher than those due to strain at the cell-substrate interface and also caused higher stressing of all parts of the cell. Significantly, this shows that the deforming effects of fluid shear stress and strain on a cellular level are qualitatively different, which may provide a basis for explaining differences in bone cell responses to both stimuli as reported in several studies. Although our approach to modeling the morphology and complex physical environment of an adherent cell is certainly simplified, our results do show independent roles for fluid flow and strain as mechanical stimuli and highlight the importance of deformation on a cellular level in bone physiology.
PUBLISHED
Keywords: cell deformation; cell biomechanics